Resource management in blockchain-enabled heterogeneous edge computing system - Ping ZHANG; Shilin LI; Yiming LIU; Xiaoqi QIN; Xiaodong XU (Tongxin xuebao)
In blockchain-enabled mobile edge computing (BMEC) systems,a new class of blockchain application related computation tasks was introduced to the system.Due to the differences of parallelism among computation tasks,heterogenous computing framework was introduced to suitably split various computation tasks on processors with vastly different processing power to achieve efficient task execution.Under the limited computation and communication resources,a system-wide utility maximization problem by jointly considering heterogeneous processor scheduling,computation and bandwidth resource allocation was formulated as a mixed-integer nonlinear programming problem.To solve the problem efficiently,the formulated problem was transformed into two sub-problems,namely application-driven heterogeneous processor scheduling and joint resource allocation,and a Lagrange-dual based algorithm was proposed.Simulation results show that the proposed scheme can effectively improve the system-wide utility of the BMEC system.